2015
DOI: 10.1155/2015/204842
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fracture Healing in Patients with Concomitant Traumatic Brain Injury: Proven or Not?

Abstract: Over the last 3 decades, scientific evidence advocates an association between traumatic brain injury (TBI) and accelerated fracture healing. Multiple clinical and preclinical studies have shown an enhanced callus formation and an increased callus volume in patients, respectively, rats with concomitant TBI. Over time, different substances (cytokines, hormones, etc.) were in focus to elucidate the relationship between TBI and fracture healing. Until now, the mechanism behind this relationship is not fully clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 133 publications
(169 reference statements)
1
57
1
Order By: Relevance
“…Though several studies have reported enhanced callus volumes post-TBI 18 19 20 21 22 , the nature of callus formation following TBI is not well established. Several researchers have speculated that the enhanced callus volumes post-TBI may represent a form of heterotopic ossification about the fracture site 16 17 31 32 33 . We observed no gross morphological differences in healing calluses between multitrauma and fracture-only mice using high resolution μCT and histology, however the contribution of heterotopic ossification to an enhanced callus formation response cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though several studies have reported enhanced callus volumes post-TBI 18 19 20 21 22 , the nature of callus formation following TBI is not well established. Several researchers have speculated that the enhanced callus volumes post-TBI may represent a form of heterotopic ossification about the fracture site 16 17 31 32 33 . We observed no gross morphological differences in healing calluses between multitrauma and fracture-only mice using high resolution μCT and histology, however the contribution of heterotopic ossification to an enhanced callus formation response cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, TBI has been associated with stimulation of osteogenesis, with heterotopic ossification (i.e. the formation of bone in soft tissues) and enhanced callus formation described in TBI patients for several decades 13 14 15 16 17 . Despite these associations the relationship between TBI and fracture healing remains poorly understood.…”
mentioning
confidence: 99%
“…The increase in glutamate levels occurs several minutes after the primary trauma, peaks in about 10 minutes and stays increased for several days [45,64]. Excitotoxicity also causes calcium influx and overload [67,68], resulting in cellular damage due to several mechanisms (i.e. activation of destructive calcium-dependent proteases, oxidative stress, mitochondrial impairment and transition pore formation, and apoptotic events) [51,53,62,[69][70][71].…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%
“…Modulating these inflammatory cells by changing their phenotype from pro-inflammatory to anti-inflammatory would likely promote therapeutic effects on TBI [42,59,98]. Additionally, peripheral injuries of the multi-injured patient may increase circulating levels of many of the inflammatory cytokines worsening TBI outcomes [13,68].…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%
“…In contrast, TBI seems to be positively correlated with osteogenesis [7][8][9]. However, this association has not been found in all studies [10,11]. Furthermore, potential pathophysiological mechanisms for TBI-related impact on osteogenesis seem to be multifactorial (humoral, hormonal and cellular) and are far from clear [7,12,13].…”
Section: Introductionmentioning
confidence: 96%